Does Ageing Matter? - Rabiul, Ahasan (2014)
The old age population has increased consistently over the last decades. If future, the increased number of old age population in the society will affect our economy. One out of every five will be an older person by 2050. One third of the people in the world are expected to be 60 years of age or older by 2150. Around 17% of US population will be 65 or older in 2020. In the developing countries, this figure will rise up to 20% or more. More than 20% of Europeans will be 65 or over by 2025. The average life expectancy is increasing with the increase in healthcare facilities and demand for standard of living around the world. In 2011, average life expectancy of an US old person (65 year of age) ranged from 10–20 years. Thus growing life expectancies of older populations have brought into question under which pension systems and other economic measures those should be designed carefully.